Equilíbrio de Nash - Davi Henrique Nazaro da Silva (2024)
This dissertation aims to deepen the study of Game Theory, with an emphasis on the concept of Nash Equilibrium. We will seek to understand how the strategic decisions of individuals or organizations interact in various contexts. The fundamental concepts of Game Theory will be presented, like the Nash Equilibrium, which allows us to identify situations of stability in non-cooperative games. Practical examples will also be explored which demonstrate the applicability of the model in real situations, such as commercial disputes and historical conflicts. By analyzing these cases, it will be possible to highlight the importance of the Nash Equilibrium as a tool for predicting and analyzing the behavior of agents in situations of interdependence.